Optimalisasi Penggunaan Obat yang Bijak dalam Keluarga dengan Program Gema Cermat - Handri Mursiti; Galau Menanti Embri; Ana Prasanti; Agnez Maysha; Vivin Rosvita; Yusuf Muamar Bashori; Yeni Farida (Pharmacon: Jurnal Farmasi Indonesia)
Self-medication practices has been widely reported in various developed and developing countries which is increasing globally so that it may potentially causes various problems. WHO emphasized that education and supervision of self-medication practices are needed. The Indonesian Ministry of Health has launched the “GeMaCerMat” program to encourage public awareness and understanding of proper drug uses. This study aims to analyzed the effect of GeMaCerMat's socialization on community knowledge and behavior about the correct use of drugs through a family approach. Survey research was conducted using questionnaire instruments and interview respondents. Respondents are Surakarta’s people in the fostered area of the Agent of GeMaCerMat (AoC) which is determined by purposive sampling. The results of the knowledge assessment before and after the intervention were compared and the differences were analyzed by paired t tests. Among 206 respondents involved,  the results show that the average respondent has very less knowledge (52.48). Posttest value indicates an increase in knowledge of the average respondent to 80.24 (good). GeMaCerMat's socialization influenced peoples’s knowledge that prooven by significant differences between pretest and postest (P=0,000; P0,05).  Behavioral assessment shows that after socialization, the average respondent has good behavior (89.02%) in applying how to get drugs, use, store and dispose of drugs properly.